Climate change and its impact on culture - Dujić, Jadranka (Crisis Management Days, 2024)
Culture, politics, and climate change are deeply connected topics that intertwine in different ways, influencing the causes and responses to climate change and shaping the causes and responses to this global challenge. Understanding these interconnections is critical to developing effective strategies to address climate change while respecting diverse cultural perspectives and political realities. Understanding the dynamics between politics and culture is critical to developing effective strategies to address the interconnected challenges of climate and cultural change. Studying this topic requires developing a conceptual framework that outlines different dimensions of culture and their potential impacts on climate change perceptions, attitudes, behaviors, and policy responses, to explore specific cultural contexts and climate change issues, identifying patterns, themes, and narratives associated with culture and climate change and the interpretation of findings on the conceptual framework, theoretical perspectives and research goals.